Historia y vigencia de las perspectivas sobre los trastornos del espectro autista - Prada-Gómez, Néstor Camilo; Reina-Martín, Diana Carolina; Rodríguez-García, Sara Sofía; Sánchez-Zocadagüi, Laura Natally (Lee La LEE, 2023)
Historia y vigencia de las perspectivas sobre los trastornos del espectro autista